Feeding increases MyoD and PCNA expression in myogenic progenitor cells of Notothenia coriiceps. - Brodeur, JC; Peck, LS; Johnston, Ian Alistair (Journal of Fish Biology, 2002)
Oxygen consumption and ammonia excretion of the Antarctic fish Notothenia corikeps (18.4 cm L-F) increased respectively two and fourfold above fasting levels 24 h after feeding with a single meal of shrimps (5.5 to 7.5% of body mass), and remained elevated for 120 h. In fasted fish, c-met positive cells in the fast muscle represented 5.5% of the total number of myonuclei. The number of c-met positive cells staining for the proliferating cell nuclear antigen was increased by 60% both 24 and 96 h after the meal, while the number of cells expressing the myogenic transcription factor, MyoD, was increased by 20% after 24 h, and by 44% after 96 h. The total numbers of c-met positive cells and cells expressing myogenin were not significantly altered 96 h following feeding. The results are consistent with an activation of myogenic progenitor cells proliferation by feeding but suggest a relatively long cell cycle time. (C) 2002 The Fisheries Society of the British Isles. Published by Elsevier Science Ltd. All rights reserved.